THE MARKET PROSPECTS OF COLONIAL PRODUCTS - Schaefer, Larissa; Junior, Silvio Santos (RACE - Revista de Administração, Contabilidade e Economia, 2016)
With the competitiveness increasing in the Brazilian agribusinesses, studies related to the survival of small farms encourage the strategy of agro-industrialization, but warn about the possibility of adulteration of the primary attributes: the traditional way of making the products. In this context, the aim of this study is to identify the importance given by the consumer to “colonial appeal” and the reasons that influence the choice for this type of product. This is a research survey, conducted with 300 families in the city of Chapecó, SC. The results show that the colonial product has a distinctive call, and that the perceptions of importance vary according to the age, confirming the findings of previous studies. Keywords: Agricultural markets. Colonial product. Consumption.